2017
DOI: 10.7897/2230-8407.08582
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Probioticated Moringa Oleifera Leaf Extract for Treatment of Anaemia Using Animal Model

Abstract: An attempt was made to evaluate anti-anaemic properties of probiotic Moringa oleifera leaf extract using animal model. Twenty four male rats were randomly assigned to four groups and all the animals were given Phenylhydrazine orally to induce anaemia. Enterococcus durans was selected as probiotic supplement. Group 1 was provided with 300mg/kg of M.oleifera leaf extract. Group 2 was supplemented with 0.3 ml of E.durans along with 300mg/kg of M. oleifera leaf extract. Group 3 and 4 were fed with E.durans and iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Abdull Razis et al [20] reported M. oleiferais' efectiveness against E. coli, Staphylococcus aureus, Bacillus subtilus, Salmonella typhi, and Proteus vulgaris. Anita et al [21] studied that moringa leaves have antidiabetic potential to prevent Type-2 diabetes in humans. Te M. oliefera leaves reduce the blood glucose level by regulating insulin release, so that it is an efective approach to manage the normal blood glucose level in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Abdull Razis et al [20] reported M. oleiferais' efectiveness against E. coli, Staphylococcus aureus, Bacillus subtilus, Salmonella typhi, and Proteus vulgaris. Anita et al [21] studied that moringa leaves have antidiabetic potential to prevent Type-2 diabetes in humans. Te M. oliefera leaves reduce the blood glucose level by regulating insulin release, so that it is an efective approach to manage the normal blood glucose level in the human body.…”
Section: Introductionmentioning
confidence: 99%